The kynurenine pathway of tryptophan catabolism and schizophrenia - Marković, Miloš (Medicinski podmladak, 2023)
The development of new therapeutic options focused on the recovery of patients with schizophrenia is primarily conditioned by elucidating the biological underpinnings of the disorder. The kynurenine pathway of tryptophan catabolism is the focus of psychiatric research since its catabolites have neuroactive properties, and one of the most important is the effect of kynurenic acid as the only endogenous NMDA receptor antagonist. According to the kynurenine hypothesis, there is an imbalance of excitatory and neuroprotective metabolites of the kynurenine pathway in patients with schizophrenia. It is postulated that excessive production of kynurenic acid leads to excessive blockade of NMDA glutamate and alpha-7 nicotinic receptors, acting as a trigger for the development of psychotic symptoms and neurocognitive deficits. This paper aims to review the kynurenine hypothesis of schizophrenia, important findings of studies exploring metabolites of the kynurenine pathway in patients with schizophrenia, and findings from the research on the potential impact of proinflammatory cytokines on the kynurenine pathway.